2019
DOI: 10.1039/c9dt00777f
|View full text |Cite
|
Sign up to set email alerts
|

Fe in biosynthesis, translocation, and signal transduction of NO: toward bioinorganic engineering of dinitrosyl iron complexes into NO-delivery scaffolds for tissue engineering

Abstract: The ubiquitous physiology of nitric oxide enables the bioinorganic engineering of [Fe(NO)2]-containing and NO-delivery scaffolds for tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 270 publications
0
58
0
1
Order By: Relevance
“…As the richest transition metal ion in humans, iron can cause a decrease in vasodilation by inhibiting the biosynthesis, transportation, transformation, and signal transduction of NO (76,77). Low ferritin and vitamin D levels have been found in adolescents with POTS (78).…”
Section: Iron Insufficiencymentioning
confidence: 99%
“…As the richest transition metal ion in humans, iron can cause a decrease in vasodilation by inhibiting the biosynthesis, transportation, transformation, and signal transduction of NO (76,77). Low ferritin and vitamin D levels have been found in adolescents with POTS (78).…”
Section: Iron Insufficiencymentioning
confidence: 99%
“…In addition to LiCl, several studies have suggested the neuroprotective properties of nitric oxide (NO) (21,22). To explore the protective functions of NO in the Drosophila model, a novel NO releasing compound, dinitrosyl iron complex [(NO)2Fe(µ-SCH2CH2OH)2Fe(NO)2] (DNIC-1), was supplemented in the food (23)(24)(25)(26). As shown in Fig.…”
Section: A Novel and Steady No-releasing Dinitrosyl Iron Complex (Dnimentioning
confidence: 99%
“…In that case, learning how these long-lived flies perform in the VBFD assay will allow us to substantiate and characterize the functional inter-connections between the peripheral tissue/organ and the central nervous system, such as the gut-brain communications (10,37,38). The design of DNIC-1 [(NO)2Fe(µ-SCH2CH2OH)Fe(NO)2], a novel NO-delivery reagent used in this study, is based on a natural motif, dinitrosyl iron unit [Fe(NO)2] for the delivery and storage of NO (23)(24)(25)(26). In comparison to the burst release of NO by the FDA-approved organic nitrates and wellstudied NONOates, DNIC-1 displays a steady kinetics for O2-triggered release of NO (half-life = 27.4 hrs at pH7.4, 22-25℃), providing a more stable source of ectopic NO under physiological conditions.…”
Section: Neural Circuits That Govern the Efficacy Of Vbfdmentioning
confidence: 99%
See 1 more Smart Citation
“…DNICs chemistry is very important in the field of biology, as well as bioinorganic chemistry. In addition, some NO bound structures have also been reported in nitric oxide reductase [14][15][16].…”
Section: Introductionmentioning
confidence: 98%